USP22 promotes gefitinib resistance and inhibits ferroptosis in non‐small cell lung cancer by deubiquitination of MDM2 - Peng Lu; Zhaoguo Li; Hang Xu (Thoracic Cancer, 2024)
Abstract Background The emergence of chemoresistance markedly compromised the treatment efficiency of human cancer, including non‐small cell lung cancer (NSCLC). In the present study, we aimed to explore the effects of ubiquitin‐specific peptidase 22 (USP22) and murine double minute 2 (MDM2) in gefitinib resistance in NSCLC. Methods Immunohistochemistry (IHC) assay, quantitative real‐time polymerase chain reaction (qRT‐PCR) assay and western blot assay were carried out to determine the expression of USP22 and MDM2. Transwell assay and flow cytometry analysis were performed to evaluate cell migration and apoptosis. Cell Counting Kit‐8 (CCK‐8) assay was employed to assess gefitinib resistance. The phenomenon of ferroptosis was estimated by related commercial kits. The oxidized C11‐BODIPY fluorescence intensity by C11‐BODIPY staining. The relation between USP22 and MDM2 was analyzed by ubiquitination assay and co‐immunoprecipitation (Co‐IP) assay. Results USP22 was abnormally upregulated in NSCLC tissues and cells, and USP22 silencing markedly repressed NSCLC cell migration and facilitated apoptosis and ferroptosis. Moreover, our results indicated that ferroptosis could enhance the suppressive effect of gefitinib on NSCLC cells. Besides, USP22 overexpression enhanced gefitinib resistance and ferroptosis protection in NSCLC cells. Mechanically, USP22 stabilized MDM2 and regulated MDM2 expression through deubiquitination of MDM2. MDM2 deficiency partially restored the effects of USP22 on gefitinib resistance and ferroptosis in NSCLC cells. Of note, we validated the promotional effect of USP22 on gefitinib resistance in NSCLC in vivo through establishing the murine xenograft model. Conclusion USP22/MDM2 promoted gefitinib resistance and inhibited ferroptosis in NSCLC, which might offer a novel strategy for overcoming gefitinib resistance in NSCLC.